Comparative Assessment of RCC Buildings with Special Moment-Resisting Frame Using Static and Dynamic Procedures of Both Linear and Nonlinear Seismic Analysis - Bhatt, Bijay; Subedi, Subodh; Ghimire, Bibek; Koirala, Sakar; Poudel, Aaditya; Panta, Nisha (Journal of Advanced College of Engineering and Management, 2026)
Advances in seismic design concepts have led to the development of sophisticated methods. The goal of this paper is to analyse the structure using different analytical procedures and compare the structural responses obtained. Linear Seismic Analysis (Response Spectrum Analysis) and Nonlinear Seismic Analysis (Pushover Analysis and Nonlinear Time History Analysis) methods were used as seismic analysis procedures. Seismic analysis was performed on the two symmetric Bare Special Reinforced Moment Frame models, having storey numbers of 5 and 10, respectively, using ETABS(v22) software. Provisions of IS 1893:2016 and ATC-40 are considered for performing Response Spectrum and Pushover analysis, respectively. Three ground motion records are provided to structural models as input to perform NTHA. The paper provides global seismic responses like storey drift and storey displacement from all procedures and concludes with a comparison of results among these procedures.